People with intellectual disabilities, relationships and sex education programmes: a systematic review - Mc Cann, Edward; Marsh, Lynne; Brown, Michael (My University, 2019)
ABSTRACT Objective: The aim of this systematic review was to examine the research evidence concerning the views and experiences of people with ID regarding their participation in and the effectiveness of RSE programmes. Methods: A systematic search of relevant electronic databases was conducted using defined inclusion criteria. All papers reviewed were from October 1998 to October 2018. The PRISMA guidelines were followed in the design and reporting of the systematic review. Results: A total of eight studies published in English were included in the review. Data were analysed and the key themes identified were (i) designing and developing RSE programmes (ii) participating in RSE programmes (iii) perceived benefits of RSE programme participation. Conclusion: This review has identified that people with ID are accessing RSE programmes and appear to find them helpful. Further research is required to investigate the extent to which programmes impact on long-term behaviour change that enables the development of sustainable relationships and reduces the unintended consequences of sexual activities. Implications for policy, practice and future research developments are discussed.
PUBLISHED
Keywords: Intellectual disability; sex education; Relationships; Intimacy; Intimacy; Relationships; Learning disability; Developmental disability; Education; Inclusive Society; INTELLECTUAL DISABILITIES; RELATIONSHIPS; RSE; Sex Education; relationship and sex education